Identification of lptA, lpxE, and lpxO, Three Genes Involved in the Remodeling of Brucella Cell Envelope - Conde-Álvarez, Raquel; Palacios-Chaves, Leyre; Gil-Ramírez, Yolanda; Salvador-Bescós, Miriam; Bárcena-Varela, Marina; Aragón-Aranda, Beatriz; Martínez-Gómez, Estrella; Zúñiga-Ripa, Amaia; de Miguel, María J.; Bartholomew, Toby Leigh; Hanniffy, Sean; Grilló, María-Jesús; et al. (Frontiers in Microbiology, 2018)
The brucellae are facultative intracellular bacteria that cause a worldwide extended zoonosis. One of the pathogenicity mechanisms of these bacteria is their ability to avoid rapid recognition by innate immunity because of a reduction of the pathogen-associated molecular pattern (PAMP) of the lipopolysaccharide (LPS), free-lipids and other envelope molecules. We investigated the Brucella homologues of lptA, lpxE, and lpxO, three genes that in some pathogens encode enzymes that mask the LPS PAMP by upsetting the core-lipid A charge/hydrophobic balance. Brucella lptA, which encodes a putative ethanolamine transferase, carries a frame-shift in B. abortus but not in other Brucella spp. and phylogenetic neighbors like the opportunistic pathogen Ochrobactrum anthropi. Consistent with the genomic evidence, a B. melitensis lptA mutant lacked lipid A-linked ethanolamine and displayed increased sensitivity to polymyxin B (a surrogate of innate immunity bactericidal peptides), while B. abortus carrying B. melitensis lptA displayed increased resistance. Brucella lpxE encodes a putative phosphatase acting on lipid A or on a free-lipid that is highly conserved in all brucellae and O. anthropi. Although we found no evidence of lipid A dephosphorylation, a B. abortus lpxE mutant showed increased polymyxin B sensitivity, suggesting the existence of a hitherto unidentified free-lipid involved in bactericidal peptide resistance. Gene lpxO putatively encoding an acyl hydroxylase carries a frame-shift in all brucellae except B. microti and is intact in O. anthropi. Free-lipid analysis revealed that lpxO corresponded to olsC, the gene coding for the ornithine lipid acyl hydroxylase active in O. anthropi and B. microti, while B. abortus carrying the olsC of O. anthropi and B. microti synthesized hydroxylated ornithine lipids. Interestingly, mutants in lptA, lpxE or olsC were not attenuated in dendritic cells or mice. This lack of an obvious effect on virulence together with the presence of the intact homologue genes in O. anthropi and B. microti but not in other brucellae suggests that LptA, LpxE or OlsC do not significantly alter the PAMP properties of Brucella LPS and free-lipids and are therefore not positively selected during the adaptation to intracellular life.